Aportación al estudio hidrológico del río Alfambra (provincia de Teruel) - Sánchez Fabre, Miguel (Geographicalia, 2017)
From the data collected in its two water level stations, the main characteristics about the behaviour of the Alfambra river flow are analysed.
Keywords: Flow; Alfambra river; Teruel.